(untitled) (CAHIERS MAGELLANES-NS, 2024)
Abstract: Political Parties are indispensable in a democratic system, and the parties are the key institutions in structuring and shaping the public policies. Few studies have focused on the issue of political parties’ preferences on climate change. Despite the pressing needs for climate mitigation and adaptation strategies, the parties seem to ignore climate change issues in domestic politics. Political parties campaign and compete for capturing power or retaining the government by adopting various means and strategies. Due to multiple factors, including unfavourable socio-economic conditions, the political parties tend not to compete on climate change and related issues in North East India, including in Manipur. The low public awareness about climate change impact and existing party preferences on traditional policy issues constrain political parties’ priority on climate change issues in Manipur. This paper discusses how significant the climate change or environmental issue is at the State Legislative Assembly elections by the political parties. It covers the qualitative and quantitative analysis of political parties’ positions during Legislative Assembly Electoral Campaigns in Manipur. An analysis of the political parties’ manifestoes and public speeches indicate important facets of the nature and direction of political change.